2013
DOI: 10.1021/ja405057n
|View full text |Cite
|
Sign up to set email alerts
|

Testing the Polynuclear Hypothesis: Multielectron Reduction of Small Molecules by Triiron Reaction Sites

Abstract: High-spin trinuclear iron complex (tbsL)Fe3(thf) ([tbsL]6− = [1,3,5- C6H9(NPh-o-NSitBuMe2)3]6−) (S = 6) facilitates 2 and 4e− reduction of NxHy type substrates to yield imido and nitrido products. Reaction of hydrazine or phenylhydrazine with (tbsL)Fe3(thf) yields triiron µ3-imido cluster (tbsL)Fe3(µ3-NH) and ammonia or aniline, respectively. (tbsL)Fe3(µ3-NH) has a similar zero-field 57Fe Mössbauer spectrum compared to previously reported [(tbsL)Fe3(µ3-N)]NBu4, and can be directly synthesized by protonation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
84
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(89 citation statements)
references
References 50 publications
2
84
2
Order By: Relevance
“…These entities are of great interest for their aesthetically beautiful structures [2][3][4], unexpected transformations [5][6][7] and potential applications in magnetism [8][9][10], luminescence [11][12][13][14][15], catalysis [16][17][18], etc. Paramagnetic transition metal CCs are of intense interest and have attracted a vast amount of attention since the discovery that some CCs behave as single-molecule magnets (SMMs) [19][20][21].…”
Section: Introduction and Reviewmentioning
confidence: 99%
“…These entities are of great interest for their aesthetically beautiful structures [2][3][4], unexpected transformations [5][6][7] and potential applications in magnetism [8][9][10], luminescence [11][12][13][14][15], catalysis [16][17][18], etc. Paramagnetic transition metal CCs are of intense interest and have attracted a vast amount of attention since the discovery that some CCs behave as single-molecule magnets (SMMs) [19][20][21].…”
Section: Introduction and Reviewmentioning
confidence: 99%
“…9 Furthermore, the resulting nitride product is cathodically shifted from the all-ferrous starting material, a result of anionic nitride ligand and the metals coming into closer proximity. 10 We hypothesized that moving from iron to cobalt would increase the basicity of the trinuclear core and make atom and group-transfer processes even more facile. To probe this we investigated the reactivity of .…”
Section: B Studies and Resultsmentioning
confidence: 99%
“…For example, his group demonstrated that a trinuclear iron complex can catalyse reductions of nitrogen compounds, such as hydrazine, requiring two or four electrons. 3 The ultimate goal would be to find a simple molecular catalyst that mimics the nitrogenase reaction, which requires six electrons for each nitrogen molecule to be split.…”
Section: Complex Chemistrymentioning
confidence: 99%